Fractures of the proximal end of the femur treated at Tishreen University Hospital in Lattakia during a full year - سعد, معن (Latakia University Journal -Medical Sciences Series, 2024)
Objectives: The aim of the present study is to evaluate the influence of various (clinical, pathological, socioeconomic) factors on the occurrence of the proximal femoral fractures. Materials and Methods: The present cross-sectional study comprises of 330 patients treated at Department of Orthopedic and Traumatic Surgery, Tishreen University Hospital, Lattakia for proximal femoral fractures between 1 July 2022- and 30 June 2023. A detailed history was taken and complete informations were collected for each patient( age, gender, place and time of fall, socioeconomic status, and associated pathology...) and then the different factors influence was studied and compared in terms of percentages. Results: Several of the above factors showed an important influence on the proximal femoral fractures, that, it was observed an important increase in occurrence of these fractures in elderly patients, females, associated pathology, and poor socioeconomic status. Conclusion: Advanced age, female gender, poor socioeconomic status, and associated pathology are risk factors for proximal femoral fractures.